The Effect of Instagram Social Media Marketing (@Baliairport) on Consumer Purchase Intention, with Brand Awareness and Online Brand Engagement as Mediating Variables - Celine Dyah Ayuning; Adhi Prasetio (International Journal Labs, 2026)
Digital promotion through social networking platforms has reshaped the way airport tenants reach and communicate with prospective buyers. At I Gusti Ngurah Rai International Airport, @baliairport, the airport's official Instagram account, is used to circulate tenant-related information and promotional content. However, strong audience reactions to promotional uploads are not always followed by an increase in tenant turnover. This gap implies that digital interaction and purchase intention occupy distinct points in the consumer decision journey, especially in airport settings where purchasing decisions are frequently made under time constraints. This research evaluates how Instagram-based Social Media Marketing relates to consumers' Purchase Intention toward airport tenants, with Brand Awareness and Online Brand Engagement examined as mediating processes. The study adopted a quantitative explanatory survey and estimated the proposed relationships with Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS. Responses were obtained from 155 qualified Instagram users through online questionnaires and direct QR-code distribution; all respondents had previously encountered tenant promotional material on @baliairport. The results confirm positive and statistically significant effects of Social Media Marketing on Brand Awareness, Online Brand Engagement, and Purchase Intention. Brand Awareness and Online Brand Engagement are likewise positively associated with Purchase Intention. Both mediators operate through complementary partial mediation. The indirect effect via Brand Awareness equals 0.191 (VAF = 33.69%), whereas the indirect path via Online Brand Engagement equals 0.118 (VAF = 23.89%). Among all structural relationships, Social Media Marketing to Brand Awareness is the strongest (B = 0.676). Overall, Instagram promotion appears particularly effective in strengthening tenant recognizability, while engagement-oriented content is more likely to support purchase consideration when tenant information remains clear, distinctive, and easy to remember.